2021
DOI: 10.1186/s12905-021-01545-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of endometriosis: a review with comparison of 8 guidelines

Abstract: Background Endometriosis, the presence of endometrial-like tissue outside the uterus, is a common clinical entity between women of reproductive age, with a prevalence of about 10%. Due to the variety of endometriosis-associated symptoms, a great variety of treatments have been implemented. The aim of this review is to give an overview on therapeutical approaches of eight national and international widely used guidelines. Methods Six national (Coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
29

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 55 publications
(43 reference statements)
1
78
0
29
Order By: Relevance
“…A variety of hormonal medications are used to suppress endometrial growth, such as contraceptive pills, GnRH agonists, and recently, a GnRH antagonist [ 18 ]. These can be used to relieve endometriosis symptoms, support the diagnosis of endometriosis, or prevent recurrence after surgery [ 19 ]. Endometriosis symptoms have a substantial impact on the physical and emotional well-being of young women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of hormonal medications are used to suppress endometrial growth, such as contraceptive pills, GnRH agonists, and recently, a GnRH antagonist [ 18 ]. These can be used to relieve endometriosis symptoms, support the diagnosis of endometriosis, or prevent recurrence after surgery [ 19 ]. Endometriosis symptoms have a substantial impact on the physical and emotional well-being of young women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study [ 17 ], reviewing eight most widely accepted guidelines concerning the management of endometriosis, most patients with endometriosis seek management because of pain and/or infertility. Though for the pain group, there is nearly an agreement on medical and conservative treatment as a 1st line option, there are controversies regarding infertility.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Yu et al [129] showed that treatment with puerarin reduced the levels of estradiol and PGE2 in endometriotic rats, by inhibiting the aromatase enzyme P450 and COX-2, in addition to increasing the expression of 17β-HSD2, thus preventing the growth of endometrial tissue. Kim et al [130][131][132][133] showed that treatment with an extract obtained from flowers of P. lobata reduced the adhesion and migration of these cells, also reducing the formation of endometriotic lesions in mice. Figure 3 summarizes the main treatment options for endometriosis.…”
Section: Puerarinmentioning
confidence: 99%